Problematic Issues of the Theory and Practice of Finger Joints Endoprosthetics (Literature Review) - Mametiev, A.O.; Naumenko , L.Yu. (TERRA ORTHOPAEDICA, 2021)
Summary. The proximal interphalangeal and metacarpophalangeal joints play an important role in the function of the hand as an organ of labor and self-care. The frequency of joint injuries of this localization reaches 32% in the structure of hand injuries, and unsatisfactory consequences are associated with the severity of the injury. Wrong treatment ranges between 60-80%, which gives ground to classify the problem as socially significant. The development and improvement of implant designs came through the introduction of new materials, structural changes in the fasteners and mobility. Much of the implants design became a thing of the past, giving a push to the development of new models. The need for anatomical and functional compliance of the implant with the characteristics of a healthy joint gave an impulse to research on the manufacture of individual prostheses with the help of 3D modeling. The analysis of literature sources showed a high level of unfavorable consequences of damage to the finger joints and the prospects for the development of more anatomical designs of hand joints prostheses. The development of individual geometrically similar designs endoprostheses of the finger joints of hand that will provide conditions of improvement of quality of treatment of patients remains an actual problem. The relatively short period of operational suitability of existing endoprostheses affected by a limited number of medical supervision necessitates the expansion of research in the near and long terms after prosthetics.